Does Foliar Application of Silicon under Natural Water Stress Conditions Increase Rice Yield in Subtropical Dry Regions? - Flores, Rilner Alves; Pessoa-de-Souza, Marco Aurélio; de Andrade, Aline Franciel; Bueno, Amanda Magalhães; de Oliveira Abdala, Klaus; de Souza Júnior, Jonas Pereira [UNESP]; de Mello Prado, Renato [UNESP]; Santos, Glenio Guimarães; Mesquita, Marcio (Springer Nature, 2021)
Silicon, although not an essential element for plant, when it is absorbed can alter cells flexibility, and then may affect plant architecture; reduce leaf senescence and deleterious effects caused by abiotic stresses. Rice is a Si accumulator, surpassing even nitrogen and potassium accumulation when compared. Thus, we evaluate the effect of foliar application of Si on the development and grain yield of upland rice. We used a randomized block design consisting of foliar application of the following five doses of Si: 0; 126.0; 252.0; 378.0; and 504.0 g ha−1 of Si applied as potassium and sodium silicate, with five replications. We balanced potassium concentrations in the solutions applied to all treatments. We divided foliar fertilization into three applications, at 30, 60, and 90 days after emergence (DAE). We evaluated foliar contents of Si and N, relative chlorophyll content (RCC), and grain yield. Si application increased silicon contents linearly, which reached 8.34 and 12.17 g kg−1 when evaluated at 60 and 90 DAE, respectively, with a dose of 504.0 g ha−1 of Si. Positive gradient of Si doses absorption represented increased grain yield by 252.0 g ha−1 of Si, and after this grain yield decreased. However, foliar silicon application up to the dose of 252.0 g ha−1 under water stress increased the grain yield of rice grown in rainfed system in approximately 9%. The application of 252.0 g of Si ha−1 promotes a grain yield (5778 kg ha−1) and also a higher differential revenue (the US $ 129.49 per hectare). The economic analysis is determined by the spraying costs.
Keywords: Beneficial element; Cerrado; Oryza sativa; Productive efficiency; Water stress